The Role of Infrastructure in Driving Economic Growth: A Qualitative Literature Study - Bado, Basri; Dunakhir, Samirah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to explore the role of infrastructure in promoting economic growth through a qualitative literature study approach. Good infrastructure is recognized as a key factor in economic development, especially in developing countries, where accessibility and efficiency are often hampered by a lack of basic facilities. This study collects and analyzes various literature sources including scientific journals, books, and policy reports to identify how infrastructure, such as transportation, energy, and telecommunications, affect economic growth. Findings from the literature show that investments in infrastructure not only improve economic efficiency and productivity, but also contribute to reducing social and economic inequality by expanding access to markets and employment opportunities. However, challenges such as resource constraints, inefficient project management and corruption often hinder the success of infrastructure projects. This study also identifies gaps in the existing literature and provides recommendations for further research and policies that can improve the effectiveness of infrastructure development. The results of this study are expected to provide greater insight into how effective infrastructure strategies can contribute to sustainable and inclusive economic growth.